2022
DOI: 10.3390/atmos13091532
|View full text |Cite
|
Sign up to set email alerts
|

Directivity of Coseismic Ionospheric Disturbances Propagation Following the 2016 West Sumatra Earthquake Using Three-Dimensional Tomography GNSS-TEC

Abstract: Ionospheric disturbances caused by the 2016 West Sumatra earthquake have been studied using total electron content (TEC) measurements by Global Navigation Satellite System (GNSS) observation stations evenly distributed in Sumatra and Java, Indonesia. Previous observation focused on the coseismic ionospheric disturbances (CID) detected 11–16 min after the earthquake. The maximum TEC amplitude measured was 2.9 TECU (TEC Unit) with speed between 1 and 1.72 km/s. A comprehensive analysis needs to be done to see ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This involves applying the ionospheric linear combination method to determine the TEC values used to generate a 3D model through tomography. Cahyadi et al (2022aCahyadi et al ( , 2022b, Muafiry et al (2018), and Muafiry and Heki (2020) observed that this method successfully calculated ionospheric disturbance models. Thus, these previous studies showed that the 3D tomography method can provide a spatial picture of ionospheric disturbances.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This involves applying the ionospheric linear combination method to determine the TEC values used to generate a 3D model through tomography. Cahyadi et al (2022aCahyadi et al ( , 2022b, Muafiry et al (2018), and Muafiry and Heki (2020) observed that this method successfully calculated ionospheric disturbance models. Thus, these previous studies showed that the 3D tomography method can provide a spatial picture of ionospheric disturbances.…”
Section: Introductionmentioning
confidence: 90%
“…Cahyadi et al. (2022a, 2022b), Muafiry et al. (2018), and Muafiry and Heki (2020) observed that this method successfully calculated ionospheric disturbance models.…”
Section: Introductionmentioning
confidence: 96%